Micro Enterprises in Nepal: Prospect and Practices - Karki, Bir Bahadur (Janapriya Journal of Interdisciplinary Studies, 2017)
The Government of Nepal (GoN), Ministry of Industry (MoI) is especially responsible for development of micro enterprises (MEs). With the support of United Nations Development Programme (UNDP), a new programme has been launching since 1998 i.e. micro enterprise development programme (MEDEP) with the aim of improve the socio economic condition of the low income families and socially excluded people in Nepal. The time between 1999 and 2011, 53345 micro enterprises are created by MEDEP in Nepal. A little more than two third i.e. 67.9 percentage micro enterprises are operated by women entrepreneurs and remaining enterprises i.e. 32.1 percentage enterprises are operated by male entrepreneurs. Out of five development region, central development region has got success to establish more MEs i.e. 15573 in number and 29.2 percentages. In the context of types of caste involved in MEs, higher number of Janajati (35.6%) are involved, then after Brahaman/Chhetri (35.3%), Dalit (22.0) and other caste (7.1%) in total. In different development region, higher numbers of Dalit (35.4 %) and other caste (15.7 %) are conducted MEs in eastern development region. Like it, higher number of Janajati (46.7%) and Brahaman/Chhetri (57.1 %) are conducted MEs in central development region and far-western development region respectively. Janapriya Journal of Interdisciplinary Studies Vol. 2, No.1 (December 2013), page: 29-36